Um olhar fenomenológico existencial para os docentes do IFES diante das dificuldades de aprendizagem de seus alunos : desvelando a inclusão dos incluídos - Castro, Mirella Guedes Lima de (2013)
This research aims to describe fenomelogical and existencially the discourses of teachers of physics, chemistry and biological areas from Ifes Campus Colatina about their living with male and female students with learning difficulties. The theoretical reference adopted was based in the researches of Paulo Freire and Elizabeth Polity, who emphasized the perspective of unveiling in others the many experiences, bringing about an understanding about the dilemmas of being a teacher of students with learning difficulties related to relationship from their local contexts. The used methodology was the existential phenomenology, insert in the ambit of qualitative approach of researching. The collecting of datum was made through individual interviews which were taken under narratives made by eight teachers of physics, chemistry and biological areas of Ifes, Campus Colatina-ES. The analyzes, however, was made through the building of guide conductors and interpretative analyze of the narrations from the persons about the studied phenomenon. The results pointed to the importance of perceiving the teacher as a subject who faces doubts and frustrations when their students do not learn according to their idealizations. They point, also, to the necessity of the educator to recognize the individual characteristics of learning of their students, looking for other methodologies to develop them at class. In the present research was made clear the much that teacher from Ifes need to know more about the processes related to the procedure of school inclusion and to attach their daily practice to them.